Adsorption of methyl red onto palladium nanoparticles loaded on activated carbon: experimental design optimization. Issue 47 (7th October 2016) - Ghaedi, M.; Hassani, R.; Dashtian, K.; Shafie, G.; Purkait, M.K.; Dehghan, H.
Abstract: In this study, palladium nanoparticles were synthesized and characterized by SEM, TEM, and BET analysis. The synthesized nanoparticles were loaded on activated carbon (Pd-NP-AC) and its adsorption efficiency was measured for methyl red (MR) removal from aqueous solution. To analyze the data, an experimental design was adopted considering three operating parameters viz. initial MR concentration, adsorbent mass, and contact time as input variables while the pH was optimized using one at a time method. Statistical analysis of data corresponded to MR holds in good agreement with predicted and experimental removal percentage. The equilibrium data followed Langmuir isotherm model, while pseudo-second-order and intraparticle diffusion models cooperatively represented experimental adsorption data at various time. High adsorption capacity was obtained because of high available surface area of the nanoparticle loaded adsorbent.